From Quezon to Bulacan: Tracing the Origin of Baliwag Buntal Hat - Guevarra, Aldrine (JPAIR Multidisciplinary Research, 2015)
Known as one of the top exporters of buntal hats, Baliwag is famous for having a Buntal Festival every month of May, the municipal seal bears a buntal hat and the town's flag carrier, the Baliwag Transit, Inc. carries with it the buntal hat as well. However, despite the importance of the industry to the local economy, the material, which is buntal fiber is coming from Quezon Province. This paper traces the origin of Baliwag Buntal Hat industry in the province of Bulacan. The study was conducted to determine the historical origin of Baliwag buntal and establish connection between the town of Baliwag and the province of Quezon, identifying the factors and circumstances on how buntal hat became one of Bulacan's traditional crafts and the symbol of the municipality of Baliwag. The methods employed are historical and descriptive and adopted the local and oral history. The historical tracing of the towns of Sariaya and Lucban are known to have wide areas of buri palm plantation, wherein buntal fibers are being extracted. Also, the technology of weaving hats is best practiced in many towns of Quezon. Baliwag also manages to carve a name on hat weaving, exporting hats abroad and creating economic potentials for the people, primarily due to the expansion, experimentation and even lamentation of the Baliwagueá¹…os. The connection provides potentials and possibilities for both Baliwag and Quezon.
Keywords: Economic history; local history; baliwag; buntal hat; Baliwag; Philippines